Textbook of receptor pharmacology - Foreman, John C.; Johansen, Torben; Gibb, Alasdair J. (Boca Raton, FL : CRC Press, 2011)
'Providing an introduction to the study of drug receptors, the Textbook of receptor pharmacology discusses quantitative descriptions of functional studies with agonists and antagonists; quantitative descriptions of ligands binding to receptors; the molecular structures of drug receptors; and the elements that transport the signal from the activated receptor to the intracellular compartment. This third edition features results from recent research on how the structure of receptors determines the interaction between the receptor and the signal transducer. This edition also offers new information on ligand binding receptor studies that use newly developed techniques'--Provided by publisher.
(Publisher-supplied data) Classical Approaches to the Study of Drug-Receptor Interactions / Donald H. Jenkinson -- Structure and Function 7-TM G-Protein Coupled Receptors / Alasdair J. Gibb -- The Structure of Ligand-Gated Ion Channels / Jan Egebjerg -- Molecular Structure of Receptor Tyrosine Kinases / IJsbrand Kramer and Michel Laguerre -- Direct Measurement of Drug Binding to Receptors / Dennis G. Haylett -- Receptors Linked to Ion Channels: Mechanisms of Activation and Block / Alasdair J. Gibb -- G-Proteins / David A. Brown -- Signal Transduction through Protein Tyrosine Kinases / IJsbrand Kramer and Elisabeth Genot -- Receptors as Pharmaceutical Targets / James W. Black.
Keywords: Receptors, Drug -- agonists; Receptors, Drug -- antagonists & inhibitors; Radioligand Assay -- methods; Receptors, Drug -- physiology; Signal Transduction -- physiology